JURIDICAL ANALYSIS OF PARTICULAR TIME WORKING AGREEMENTS TO REALIZE THE PROTECTION OF WORKERS' RIGHTS AND WELFARE: RESEARCH STUDY AT THE OFFICE OF PT. BERSAMA GEMILANG PROPERTY BATAM - Andriani, Dian; Washliati, Laily; Fadjriani, Lia; Milanie, Feby; Saifannur, Andri (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2021)
Juridical Analysis of a Specific Time Work Agreement (PKWT) to Realize the Protection of Workers' Rights and Welfare (Research Study at the PT. Bersama Gemilang Property Batam Office), has been carried out as it should, in accordance with Law Number 11 of 2020 concerning Job Creation. There are factors related to the protection of the rights and welfare of contract workers. The qualifications/types of writing in this journal use normative legal writing, and then integrate it with sociological/empirical legal writing, and to analyze some of the problems in this journal, Lawrence M. Friedmen's big theory, Jeremy Bentham's middle theory, and application theory are used. / applied theory Mochtar Kusumaatmadja. The results of the analysis are still experiencing several obstacles both internally and externally. The obstacles faced have not been the implementation of rights and welfare, which have been prioritized and carried out but not yet perfectly. It is very necessary and improved in terms of supervision in terms of quality and quantity in order to suppress and not give space to violators who do not comply with contract workers. There is also a need for wider socialization in a timely manner regarding the implementation of the new law on the rights and welfare of contract workers.